Analisis Kesesuaian Pengungkapan Aspek Emisi Karbon pada Industri Pertambangan Batubara berdasarkan GRI Standards pada Laporan Keberlanjutan Tahun 2020-2022 - Pratama, Peter Lim; Permatasari, Paulina (Universitas Pendidikan Ganesha, 2024)
Coal mining requires a source of energy to operate its business. The energy sources used can be renewable energy and conventional energy. Conventional energy use can harm the environment and generate emissions. Continuously generated emissions can trigger global warming that can have a negative impact on the environment. One of the precautions Indonesia has taken to mitigate the effects of global warming is to require the Limited Liability Company to publish sustainability reports. Companies in producing sustainability reports can use the Global Reporting Initiative (GRI) standard as one of the sustainability reporting guidelines. The research method used is qualitative descriptive. The data source used is secondary data in the form of sustainability reports that have been published by Limited Liability Company. The sample data used is a coal industry mining sector company listed on the Indonesian Stock Exchange which has issued a sustainability report for 2020-2022. The data processing techniques used are content analysis techniques that are given scoring based on GRI Standard requirements. The results of the emission relevance analysis in the sustainability report of the coal mining industry in 2020-2022 have a percentage: 31,8% in 2020, 43,75% in 2021, and 48% by 2022.